A theory of multihoming in rideshare competition. Issue 1 (8th January 2019) - Bryan, Kevin A.; Gans, Joshua S.
Abstract: We examine competition among ridesharing platforms, where firms compete on both price and the wait time induced with idled drivers. We show that when consumers are the only agents who multihome, idleness is lower in duopoly than when consumers face a monopoly ridesharing platform. When drivers and consumers multihome, idleness further falls to zero as it involves costs for each platform that are appropriated, in part, by their rival. Interestingly, socially superior outcomes may involve monopoly or competition under various multihoming regimes, depending on the density of the city, and the relative costs of idleness versus consumer disutility of waiting.